Worming its way in—Polydora websteri (Annelida: Spionidae) increases the number of non-indigenous shell-boring polydorin pests of cultured molluscs in South Africa - Rodewald, Nicola; Snyman, Reinette; Simon, Carol A. (Zootaxa, 2021)
Polychaete worms of the Polydora-complex (commonly referred to as polydorins) include some of the most common pests of cultured molluscs. Modern culture of molluscs, particularly oysters, is associated with large-scale movement of stock which facilitates movement of polydorins either as “hitchhikers” on the transported molluscs or in the packaging. In 2009, a species identified as Polydora cf. ciliata Johnston, 1838 was reported from oysters in a culture facility in Port Elizabeth, South Africa. Since then, more specimens of this species were recorded on farmed oysters from Namibia, Kleinzee and Paternoster on the west coast of South Africa, but tentatively reidentified as Polydora cf. websteri Hartman in Loosanoff and Engle, 1943 based on morphology and limited genetic evidence. The main aim of this study is therefore to clarify the identity of these specimens by integrating morphological and genetic (mitochondrial COI, Cyt b and nuclear 18S rRNA) evidence. Specimens from South Africa match the morphology of the lectotype of P. websteri and are morphologically and genetically very similar to P. websteri from Australia, China, Japan, and the east, gulf and west coasts of the USA. This confirms the presence of P. websteri in South Africa, making this the second most widespread polydorin pest of aquaculture known. Understanding the full distribution range of the species will help to better understand its global route of invasion and consequently assist with preventing or at least minimising further spread. Polydora websteri increases the number of polydorin pests in South Africa to seven.